ANALYSIS OF THE MAIN APPLIED METHODS OF PUBLIC OPINION RESEARCH - Fayzieva Farogat Baxtiyorovna; Mahmudova Muslima Maʼrufjon qizi; Mahmudova Muslima Maʼrufjon qizi (Journals Park Publishing, 2024)
Methods of studying public opinion are crucial for understanding the opinions, views and beliefs of the general public. The article analyzes the methods of public opinion research, and the importance of these methods in the study of public opinion. In addition, the works of Abu Mansour al-Moturidi, Abu Nasr Farabi, Abu Rayhan Beruni, Amir Temur and Alisher Navoi analyzed scientific approaches to the study of social processes in society using special methods to achieve effective management by taking into account the opinions of the population in society and public administration.
Keywords: Surveys, public opinion, sociological research, marketing research, measuring public opinion, analysis, expert, сontent analysis, document analysis method, face-to-face interview, (CATI) telephone survey, FGD, public survey, politics and decision-making, social, cultural, general public.